Reversible splenial lesion syndrome in neuroleptic malignant syndrome. - Al-Edrus, Sharifah Aishah; Norzaini, R.; Chua, R.; Puvanarajah, S. D.; Shuguna, M.; Muda, Ahmad Sobri (University of Malaya, 2009)

(untitled)
Background: Reversible focal lesions in the splenium of the corpus callosum (SCC) or reversible splenial lesion syndrome are rare and little is known about their pathophysiology.